The Neutrosophic Poisson Distribution Applied to Horadam Polynomial-Subordinate Bi-Univalent Functions (European Journal of Pure and Applied Mathematics, 2025)
In the open unit disk, we introduce a new subclass of analytic and bi-univalent functions described by the Neutrosophic Poisson distribution series. The estimates for the Fekete--Szegö type and the Taylor coefficients. Then, using the Horadam polynomials, the inequalities corresponding to the functions that belong to this recently discovered subclass are investigated. Along with some corollaries, we also go over the implications of the findings presented in this essay. Numerous branches of mathematics, science, and technology are anticipated to heavily rely on the neutrophilic Poisson distribution.
Keywords: Horadam polynomials, bi-univalent functions, analytic functions, Fekete-Szegö problem